2017
DOI: 10.14744/nci.2017.15013
|View full text |Cite
|
Sign up to set email alerts
|

Clinical approach to pediatric neck masses. Retrospective analysis of 98 cases

Abstract: OBJECTIVE:Pediatric neck masses (PNMs) are a frequently encountered problem in otorhinolaryngology practice. The clinical approach to cervical masses in childhood varies from that of adults. Due to differences among clinicians in the assessment of a PNM, studies investigating this subject are significant contributions to the literature. For this reason, a review was conducted of pediatric PNM cases with an open biopsy (incisional/excisional) and a histopathological diagnosis.METHODS:The hospital records of 98 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 16 publications
0
18
0
6
Order By: Relevance
“…Acquired LNM had solid US appearance significantly more frequently than congenital ones, and it was substantiated by the high sensitivity of the US as diagnostic examination. It was previously reported that high percentage of LNM in children (45%) were solid [ 1 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Acquired LNM had solid US appearance significantly more frequently than congenital ones, and it was substantiated by the high sensitivity of the US as diagnostic examination. It was previously reported that high percentage of LNM in children (45%) were solid [ 1 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Forty-one of all our patients presented with LNM (16,4%) had malignancies, thirty-one having lymph node malignancy, while ten had tumors of other origin ( Table 2 ). Other studies report malignancies in 12% to 15% of all neck masses [ 1 , 2 ]. In general pediatric population examined by primary care providers due to persistent lymph node enlargement, surgical biopsy showed malignancy in 15% to 22% [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasound has been reported to have 95% sensitivity and 83% specificity in the differentiation between malignant and reactive lymph nodes7 ; malignancy (lymphoma) is more likely with an abnormally shaped, homogeneous, hypoechoic lymph node, compared with a heterogeneous lymph node that retains its normal architecture, with surrounding inflammation and central liquefaction (typical of inflamed/infected lymph nodes) 8. CT and MRI can provide more detailed information about the anatomical location, lesion characteristics and surrounding structures 6…”
Section: Commentary: Neck Lumpsmentioning
confidence: 99%
“…Majority of the time, anamnesis and physical examination is sufficient to establish the diagnosis, but when diagnosis can't be made additional FNAC and radiology of swelling are required. 11 Judicious use of investigations may avoid the unnecessary stress and anxiety for the treating doctor and parents. 12 Treatment of infective neck swelling can be done by conservative method and/or surgical methods.…”
Section: Introductionmentioning
confidence: 99%